2008
DOI: 10.1364/ol.34.000001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of phosphor geometry on the luminous efficiency of high-power white light-emitting diodes with excellent color rendering property

Abstract: High-power white light-emitting diodes (LEDs) are fabricated by combining blue LEDs and green (Ba,Sr)(2)SiO(4):Eu(2+) and red CaAlSiN(3):Eu(2+) phosphors with varying phosphor geometry. The white LED having separated the phosphor layer by the silicone gel layer between green and red phosphor layers shows superior optical properties. The luminous efficiency (eta(L)) is improved by a decrease of reabsorption of green light by red phosphor owing to a difference among refractive indices. The white LED shows very h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
34
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(37 citation statements)
references
References 14 publications
0
34
0
Order By: Relevance
“…Compared to incandescent and fluorescent lamps, white LEDs have many advantages, such as a long lifetime, high efficiency, and lower energy consumption [1]. Most white LEDs use phosphors excited by diode chips with short wavelengths (blue or violet) to reemit a broad spectrum light with a good color-rendering index [2][3][4]. Since the optical performance of LED lighting, including the correlated color temperature (CCT) values, is strongly dependent on the thickness, combination concentration, and geometrical distribution of the phosphors, the commercially available recipes for white LEDs usually require careful manipulation if they are to meet the CCT requirements.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to incandescent and fluorescent lamps, white LEDs have many advantages, such as a long lifetime, high efficiency, and lower energy consumption [1]. Most white LEDs use phosphors excited by diode chips with short wavelengths (blue or violet) to reemit a broad spectrum light with a good color-rendering index [2][3][4]. Since the optical performance of LED lighting, including the correlated color temperature (CCT) values, is strongly dependent on the thickness, combination concentration, and geometrical distribution of the phosphors, the commercially available recipes for white LEDs usually require careful manipulation if they are to meet the CCT requirements.…”
Section: Introductionmentioning
confidence: 99%
“…Won et al have demonstrated the strong influence of phosphor geometry on the lumen output of LED lamps with higher color rendering index (CRI) by adding green (Ba,Sr) 2 SiO 4 :Eu 2+ and red CaAlSiN 3 :Eu 2+ phosphors with various phosphor structures to the blue LEDs [4]. Oh et al have proposed G-A-R multi-package LED, which provides higher lumen output and good CRI [5]. Zheng et al have enhanced the CRI of the LED lamp by using multi-chromatic phosphor [6].…”
Section: Introductionmentioning
confidence: 99%
“…For the cool WLED at approximately 5000~5500 K, the YAG:Ce phosphor is used to generate the yellow light when pumped by blue source [14]. To achieve the warm WLED at approximately 2700~3000 K, the red phosphor such as nitride-based phosphor is adopted in package and past results have delivered high color-rendering index (CRI) devices [15,16]. However, the red phosphor suffered from the larger stoke shift and causes the cascade excitation process in warm WLEDs, resulting in lower lumen efficiency [17].…”
Section: Introductionmentioning
confidence: 99%